Protoplast fusion studies in Ocimum species - Kholgade, Nitish; Mohta, Vijay; Mathew, Rebecca; Sankar, P. Deepa (Research in Biotechnology, 2013)
Protoplasts of three Ocimum species, viz., O. basilicum, O. sanctum and O. gratissimum derived from leaf samples were used for studying fusion. The isolation of protoplasts were carried out using 1 % cellulase and 0.5 % pectinase in combination with Cocking-Peberdy-White (CPW)Ã¢â‚¬â€œ13% mannitol solution as it gave the best results.Ã‚Â The protoplasts obtained by enzymatic digestion were purified by centrifugation.Ã‚Â The yield of protoplasts was found to be highest when centrifuged at 800 rpm for 15 minutes at 4Ã‚ÂºC. AmongÃ‚Â theÃ‚Â fusogenÃ‚Â combinationsÃ‚Â triedÃ‚Â toÃ‚Â obtainÃ‚Â homokaryons,Ã‚Â 40Ã‚Â %Ã‚Â Polyethylene glycol (PEG)-6000Ã‚Â fusogen solution gave betterÃ‚Â results whenÃ‚Â comparedÃ‚Â toÃ‚Â the otherÃ‚Â combinations. The Ca2+ concentration and pH level (5-9) were altered and studied but major changes in time taken for fusion were not observed.Ã‚Â The mean count of protoplasts per ml was found to be 209,200 for O. basilicum, 317,500 for O. gratissimum and 502,500 for O. sanctum. The Evans blue staining test showed that the average percentage of viable cells was 52.8 % for O. basilicum, 52.54 % for O. sanctum and 47.15 % for O. gratissimum.